The Mediating Effect of Coping Style in the Relationship Between Depression and Disordered Eating Among Chinese Female Undergraduates - Zheng, Zheng; Han, Wenyue; Li, Yawen; Wang, Dongyan; Gu, Simeng; Wang, Fushun (Frontiers in Psychology, 2020)
The aim of the current study was to explore the relationship between depression and disordered eating in female undergraduates and the mediating role of coping style between depression and disordered eating. Self-report questionnaires assessing coping style, disordered eating, and depression were completed in 646 Chinese female undergraduates. The results illustrated that there were obvious differences in disordered eating among the undergraduates with various majors. The disordered eating in female undergraduates majoring in art was more serious than those in other majors. Depression and coping style were effective indicators to predict disordered eating. Moreover, depression could not only directly predict disordered eating, but also predict disordered eating through the mediating effect of coping style. These findings indicate that depression and negative coping style are associated with disordered eating. Coping style could mediate the effect of depression on disordered eating, as these may be an important target for early intervention programs for eating disorder.